Comparison of high‐performance liquid chromatography/tandem mass spectrometry and high‐performance liquid chromatography/photo‐diode array detection for the quantitation of carotenoids, retinyl esters, α‐tocopherol and phylloquinone in chylomicron‐rich fractions of human plasma. (7th May 2013) - Kopec, Rachel E.; Schweiggert, Ralf M.; Riedl, Ken M.; Carle, Reinhold; Schwartz, Steven J.
<x xml:space="preserve">Abstract</x> RATIONALE Bioavailability of essential lipophilic micronutrients and carotenoids is of utmost interest for human health, as the consumption of these compounds may help alleviate major nutritional deficiencies, cardiovascular disease, and cancer. High‐performance liquid chromatography/photo‐diode array detection (HPLC‐PDA) and high‐performance liquid chromatography/tandem mass spectrometry (HPLC/MS/MS) were compared for the quantitative analysis of α‐ and β‐carotene, β‐cryptoxanthin, lutein, lycopene, α‐tocopherol, phylloquinone, and several retinyl esters from chylomicron‐containing triglyceride rich lipoprotein (TRL) fractions of human plasma obtained from two clinical trials. METHODS After selecting an efficient extraction method for the analytes, both the HPLC/PDA and the HPLC/MS/MS methods were developed and several parameters validated using an HP 1200 series HPLC system interfaced with a HP 1200 series diode‐array detector (Agilent Technologies, Santa Clara, CA, USA) and a QTRAP 5500 (AB Sciex, Foster City, CA, USA) via an atmospheric pressure chemical ionization (APCI) probe operated in positive ion mode. RESULTS For lycopene, α‐ and β‐carotene, HPLC/MS/MS was up to 37 times more sensitive than HPLC‐PDA. PDA detection was shown to be up to 8 times more sensitive for lutein. MS/MS signals were enhanced by matrix components for lutein and β‐cryptoxanthin, as determined by referencing to the matrix‐independent PDA signal. In contrast, matrix suppression was observed for retinyl palmitate, α‐carotene, and β‐carotene. Both detectors showed similar suitability for α‐tocopherol, lycopene and retinyl palmitate (representing 73% of total retinyl esters). MS/MS exclusively allowed the quantitation of minor retinyl esters, phylloquinone, and (Z)‐lycopene isomers. CONCLUSIONS HPLC/MS/MS was more sensitive than HPLC‐PDA for six of the eight analytes and represents a powerful tool for the analysis of chylomicron samples and potentially other biological samples of limited sample size. When internal standards are available for the target carotenoid, employing MS/MS detection may reduce the necessary blood sample volume, which is particularly advantageous for minimizing risk and discomfort to human subjects during clinical studies. Copyright © 2013 John Wiley & Sons, Ltd.